3x - 2x = 7
x = 7
2006-11-12 05:32:32
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
7
2006-11-13 18:58:23
·
answer #2
·
answered by silent rain 2
·
0⤊
0⤋
x=7
2006-11-12 05:30:40
·
answer #3
·
answered by patriotsfan 2
·
0⤊
0⤋
x=7
2006-11-12 05:30:29
·
answer #4
·
answered by 7
·
0⤊
0⤋
x=7
2006-11-12 05:29:21
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
x=7
2006-11-12 05:29:12
·
answer #6
·
answered by 77684 3
·
0⤊
0⤋
x=7
2006-11-12 05:29:01
·
answer #7
·
answered by cool nerd 4
·
0⤊
0⤋
If I remove "the x term" from the RHS ( the x term being 2x ) , I get :
3x = 7 , so x = 7/3 or 2.3333
If I remove only "x" from the RHS , I get :
3x = 2 + 7 so x = 3
2006-11-12 05:41:26
·
answer #8
·
answered by Duke_Neuro 2
·
0⤊
0⤋
3x=2x + 7
-2x -2x
x=7
The 7 will stay on the right hand side. Subtract a 2x from each side so that the left reads "3x - 2x" and the right reads "2x -2x". This will balance out the equation, and you'll end up with x=7.
2006-11-12 05:30:54
·
answer #9
·
answered by quatrapiller 6
·
0⤊
0⤋
3x = 2x + 7
-2x=-2x
x=7
3*7=2*7+7
21=21
2006-11-12 06:20:34
·
answer #10
·
answered by ikeman32 6
·
0⤊
0⤋